Study of the current vegetation of the historical lava flows of the Arafo Volcano, Tenerife, Canary Islands, Spain - Martín Osorio, Victoria Eugenia; Wildpret Martín, Wolf Hermann; Negrín, Rocío González; de la Torre, Wolfredo Wildpret (Mediterranean Botany, 2020)
Vegetation research on the lava flows of the historic volcanic eruption of 1705 in Arafo, Tenerife, Canary Islands, is presented. The study area located in the 830000-year-old valley of Güímar was created after a massive landslide 47 km3 in volume. The research is divided into three parts, which cover an altitudinal range from around 35 to 1583 m a.s.l. from the Lower-semiarid Inframediterranean up to the Lower-dry lower-Mesomediterranean bioclimatic belts. First, a phytosociological study of the vegetation present in the area was made and concluded that richness in pioneer communities form a vegetation complex with a high degree of endemicity. Two new associations and four pioneer communities are proposed. Especially notable are the communities of Stereocauletum vesuviani and the pioneer communities of Pinus canariensis. The second part of the research was a field sampling study of 450 individuals of Pinus canariensis, which were measured at different altitudes to obtain data about the colonization dynamics of this species on this 300 years old substrate. We found that stem diameter seems to be a good indicator for healthy tree development at a range between 700 to 1300 m asl, which corresponds to the pine forest as potential vegetation and that many individuals show signs of nutrient deficiency. The third part consists of the publication of two new populations of the Canarian endemism Himantoglossum metlesicsianum, a highly endangered orchid. The monitoring of these two populations has recently begun, and further research will be conducted on all three aspects of this publication, which will be presented and expanded upon in the future.